1987
DOI: 10.1038/328082a0
|View full text |Cite
|
Sign up to set email alerts
|

The human tumour-associated epithelial mucins are coded by an expressed hypervariable gene locus PUM

Abstract: A single highly-polymorphic autosomal gene locus PUM codes for a family of mucin-type glycoproteins, separable by SDS-gel electrophoresis, which we first identified in human urine. The locus also codes for glycoproteins which are abundant in several other normal epithelial tissues and body fluids, including milk, and in tumours of epithelial origin. These mucin-type glycoproteins seem to be very immunogenic in rodents and, in a search for epithelial specific or tumour-associated antigens, a large number of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
0
4

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(95 citation statements)
references
References 0 publications
3
88
0
4
Order By: Relevance
“…Solubilised StMPM protein fractionated over S200 Sephacryl in the presence of detergent. Fractionated 5T4 antigenicity assessed in ELISA family of mucin type glycoproteins (Swallow et al, 1987), but with clear differences from those defined by the CA or HMFG series of antigens (Wiseman et al, 1984;Burchell et al, 1983). These latter glycoproteins are defined by several monoclonal antibodies which have been shown to be reactive with a wide range of malignant tumour cells but also reactive with certain specialised normal epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Solubilised StMPM protein fractionated over S200 Sephacryl in the presence of detergent. Fractionated 5T4 antigenicity assessed in ELISA family of mucin type glycoproteins (Swallow et al, 1987), but with clear differences from those defined by the CA or HMFG series of antigens (Wiseman et al, 1984;Burchell et al, 1983). These latter glycoproteins are defined by several monoclonal antibodies which have been shown to be reactive with a wide range of malignant tumour cells but also reactive with certain specialised normal epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…It has a centrally located tandem repeat (TR) domain (Lan et al, 1985;Gendler et al, 1987Gendler et al, , 1988Gendler et al, , 1990Swallow et al, 1987;Hareuveni et al, 1990) comprised of 20 -120 or more repeat units of 60 nucleotides, which encode 20 amino acids. The repeating units include several serine and threonine residues, which carry most of the glycosylation, and this glycosylation, as well as the general pattern of expression, is altered in cancerous cells (Taylor-Papadimitriou et al, 2002).…”
mentioning
confidence: 99%
“…That the mucin was detectable in low levels in the pooled sera of normal individuals (Figure 2) In SDS polyacrylamide gels, PEM migrates as a series of bands differing slightly in electrophoretic mobility. This is due to the polymorphism which is seen at both the DNA and protein level (Swallow et al, 1987;Gendler et al, 1987). Each band represents one of several phenotypes which are the products of a number of codominant alleles present at a single gene locus.…”
Section: Purification Of Circulating Pemmentioning
confidence: 99%
“…Originally purified from human milk, this component has been termed PAS-O by Shimizu and Yamauchi (1982), EMA (epithelial membrane antigen) by Heyderman et al, (1979), by Hilkens et al (1984) and MSA (mammary serum antigen) by Stacker et al (1988). Karlsson et al (1983) first reported that the mucin exhibits a genetic polymorphism which was later shown to exist at both the protein and DNA level (Swallow et al, 1987;Gendler et al, 1987, respectively). Consequently, Gendler et al, (1988) have named the mucin polymorphic epithelial mucin, or PEM, a term which aptly describes its properties.…”
mentioning
confidence: 99%